2021
DOI: 10.1177/1839334921999500
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Generation Y Consumers Adopt Online Luxury Technologies: A Values Approach

Abstract: This paper investigates how luxury values act as antecedents of Generation Y consumer’s adoption of online luxury purchasing technologies. Research findings based on 509 Generation Y luxury consumers in Turkey reveal that well-accepted luxury consumer values-namely functional, hedonic, social values -as well as product availability play a significant role on Generation Y consumers’ acceptance of online luxury purchasing technologies. Price consciousness value, which is an essential consumer value of online mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 111 publications
(193 reference statements)
0
14
0
Order By: Relevance
“…Being collectivist in nature, the Indian consumer constantly seeks validation and looks for fitting-in behavior in social settings (Shukla, 2011); therefore it can be concluded that this consumption pattern is highly dependent on social cues and societal acceptance. Luxury apparel brands are consumed for social/public display because they can easily employ to signal wealth (Li et al, 2012;Erdogmus et al, 2021). Han et al (2010) observed that the consumers who have an innate desire to be associated with a certain group would signal their wealth and belongings, whereas consumers who are low in need for status purchase luxury brands but do not to signal it or display their wealth.…”
Section: Discussionmentioning
confidence: 99%
“…Being collectivist in nature, the Indian consumer constantly seeks validation and looks for fitting-in behavior in social settings (Shukla, 2011); therefore it can be concluded that this consumption pattern is highly dependent on social cues and societal acceptance. Luxury apparel brands are consumed for social/public display because they can easily employ to signal wealth (Li et al, 2012;Erdogmus et al, 2021). Han et al (2010) observed that the consumers who have an innate desire to be associated with a certain group would signal their wealth and belongings, whereas consumers who are low in need for status purchase luxury brands but do not to signal it or display their wealth.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, “Topic 8 (Online engagement)” refers to customer online behavior, which has been a topical area in marketing. This is reflected in research about understanding customer experience and online reviews (Robertson et al, 2021), and customer adoption of online technologies (Erdogmus et al, 2021). On the other hand, “Topic 9 (Purchase intention),” “Topic 13 (Retail resources),” and “Topic 15 (Trust)” centers on determinants of relationship quality and relationship outcomes.…”
Section: Topic Modelingmentioning
confidence: 99%
“…"This target group will explore the products they buy before achieving the purchasing process, whether it takes place in a digital or physical environment, and will do so again online." [24].…”
Section: Distribution Of Luxury Fashion Brands Through Digital Channelsmentioning
confidence: 99%